GABA(A) receptor activation in the lateral parabrachial nucleus induces water and hypertonic NaCl intake - Callera, J. C.; Oliveira, L. B.; Barbosa, S. P.; Colombari, DSA; De Luca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2005)
Inhibitory serotonergic and cholecystokinergic mechanisms in the lateral parabrachial nucleus and central GABAergic mechanisms are involved in the regulation of water and NaCl intake. In the present study we investigated if the GABA(A) receptors in the lateral parabrachial nucleus are involved in the control of water, NaCl and food intake in rats. Male Holtzman rats with stainless steel cannulas implanted bilaterally into the lateral parabrachial nucleus were used. Bilateral injections of muscimol (0.2 nmol/0.2 mu l) into the lateral parabrachial nucleus strongly increased 0.3 M NaCl (20.3 +/- 7.2 vs. saline: 2.6 +/- 0.9 ml/180 min) without changing water intake induced by the treatment with the diuretic furosemide combined with low dose of the angiotensin converting enzyme inhibitor captopril s.c. In euhydrated and satiated rats, bilateral lateral parabrachial nucleus injections of muscimol (0.2 and 0.5 nmol/0.2 0) induced 0.3 M NaCl intake (12.1 +/- 6.5 and 32.5 +/- 7.3 ml/180 min, respectively, vs. saline: 0.4 +/- 0.2 ml/180 min) and water intake (5.2 +/- 2.0 and 7.6 +/- 2.8 ml/ 180 min, respectively, vs. saline: 0.8 +/- 0.4 ml/180 min), but no food intake (2 +/- 0.4 g/240 min vs. saline: 1 +/- 0.3 g/240 min). Bilateral lateral parabrachial nucleus injections of the GABAA antagonist bicuculline (1.6 nmol/0.2 mu l) abolished the effects of muscimol (0.5 nmol/0.2 mu l) on 0.3 M NaCl and water intake. Muscimol (0.5 nmol/0.2 mu l) into the lateral parabrachial nucleus also induced a slight ingestion of water (4.2 +/- 1.6 ml/240 min vs. saline: 1.1 +/- 0.3 ml/240 min) when only water was available, a long lasting (for at least 2 h) increase on mean arterial pressure (14 +/- 4 mm Hg, vs. saline: -1 +/- 1 mm Hg) and only a tendency to increase urinary volume and Na+ and K+ renal excretion. Therefore the activation of GABAA receptors in the lateral parabrachial nucleus induces strong NaCl intake, a small ingestion of water and pressor responses, without changes on food intake. (c) 2005 Published by Elsevier Ltd on behalf of IBRO.
Keywords: muscimol; sodium appetite; thirst; blood pressure; satiety